2021
DOI: 10.1111/imr.12949
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the rules for B cell selection

Abstract: The autoimmune checkpoint during B cell maturation eliminates self-antigen reactive specificities from the mature B cell repertoire. However, an exception to this rule is illustrated by B-1 cells, an innate-like self-reactive B cell subset that is positively selected into the mature B cell pool in a self-antigen-driven fashion. The mechanisms by which B-1 cells escape central tolerance have puzzled the field for decades. A key clue comes from their restricted developmental window during fetal and neonatal life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 88 publications
2
10
0
Order By: Relevance
“…B surface Ag Inact. Poliovirus Hib polysaccharide •CRI as a non-specific self-limiting stress reaction especially in most vulnerable infants [ 14 , 34 37 ] but no difference in CRI-rates in RCT between DTaP exposed and unexposed PIs [ 38 40 ] •post-immunization fever: 1.4%—33% [ 13 , 41 43 ] RCTs: [ 38 , 44 ] •excellent immunogenicity of most hexavalent components across all GA- and BW- groups [ 14 , 45 ] •inconclusive reports for pertussis and Hib vaccines [ 45 48 ] •Lower response of PIs to certain polio serotypes [ 14 , 49 - 51 ], Hib [ 52 54 ] and HBV [ 15 17 , 19 , 55 ] no RCTs •AAP/AGH/WHO/GOC: immunization of PIs according to chronological age without correction for prematurity •AGH: extra dose of Hib for ELGANs or VLBWI at 6 months of age depending on the vaccine used Pneumococcal vaccine (intramuscular) Conjugate vaccines (i.e., PCV13) Polysaccharide vaccines (i.e., PPSV23) •safe and well tolerated by PI [ 56 , 57 ] •comparable rate of AEs after immunization (compared to FTI) [ 58 , 59 ] •no serious, vaccine-related AEs reported RCTs: [ 56 ] •inconclusive results: GA-dependent specific IgG antibody titers [ 61 ] •reduced but protective responses to certain PCV serotypes [62,57,63,64 (importance of a booster dose [ 62 ]) •significant reduction in IPD in birth cohorts of PI [ 65 ] and up to 100% efficacy for PI and LBWI [ 59 , 60 ] RCTs: [ 56 ] •AGH/GOC: P...…”
Section: Safety Tolerability and Efficacy Of Vaccines Administered To...mentioning
confidence: 99%
See 3 more Smart Citations
“…B surface Ag Inact. Poliovirus Hib polysaccharide •CRI as a non-specific self-limiting stress reaction especially in most vulnerable infants [ 14 , 34 37 ] but no difference in CRI-rates in RCT between DTaP exposed and unexposed PIs [ 38 40 ] •post-immunization fever: 1.4%—33% [ 13 , 41 43 ] RCTs: [ 38 , 44 ] •excellent immunogenicity of most hexavalent components across all GA- and BW- groups [ 14 , 45 ] •inconclusive reports for pertussis and Hib vaccines [ 45 48 ] •Lower response of PIs to certain polio serotypes [ 14 , 49 - 51 ], Hib [ 52 54 ] and HBV [ 15 17 , 19 , 55 ] no RCTs •AAP/AGH/WHO/GOC: immunization of PIs according to chronological age without correction for prematurity •AGH: extra dose of Hib for ELGANs or VLBWI at 6 months of age depending on the vaccine used Pneumococcal vaccine (intramuscular) Conjugate vaccines (i.e., PCV13) Polysaccharide vaccines (i.e., PPSV23) •safe and well tolerated by PI [ 56 , 57 ] •comparable rate of AEs after immunization (compared to FTI) [ 58 , 59 ] •no serious, vaccine-related AEs reported RCTs: [ 56 ] •inconclusive results: GA-dependent specific IgG antibody titers [ 61 ] •reduced but protective responses to certain PCV serotypes [62,57,63,64 (importance of a booster dose [ 62 ]) •significant reduction in IPD in birth cohorts of PI [ 65 ] and up to 100% efficacy for PI and LBWI [ 59 , 60 ] RCTs: [ 56 ] •AGH/GOC: P...…”
Section: Safety Tolerability and Efficacy Of Vaccines Administered To...mentioning
confidence: 99%
“…•significant reduction in IPD in birth cohorts of PI [ 65 ] and up to 100% efficacy for PI and LBWI [ 59 , 60 ]…”
Section: Safety Tolerability and Efficacy Of Vaccines Administered To...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Lin28B gene is negatively regulated by miRNAs (such as miR-26) and its overexpression is linked to the repression of let-7 miRNAs [44]. A previous publication also showed that Lin28b serves as a molecular switch for tuning the tolerance threshold during B cell receptor (BCR) repertoire selection early in life [45]. Therefore, it is enticing to speculate that this protein may contribute to the development of SSc, in which the appearance of autoantibodies is the first clinical phenomenon observed.…”
Section: Supplementary Materialsmentioning
confidence: 99%